IMPROVING THE PRACTICE OF ENSURING THE ECONOMIC SECURITY OF ENTERPRISES (World Bulletin of Management and Law, 2024)
The economic activity of enterprises in real time is carried out in a transformational environment, characterized by reforms in the political, economic, social spheres of life and the formation of a new worldview on the development of economic systems. In such conditions, the security system of the enterprise becomes especially important. The analysis of theoretical and methodological approaches of the disclosure of the essence of economic security of an enterprise in a turbulent environment and digitalization of the economy has identified six vectors of modern scientific achievements deal the economic security of the enterprise